Cultivo in vitro e criopreservação de Alibertia sp. - Sarto, Marisa Taniguchi (2015)
The genus Alibertia has native fruit species of the Cerrado that have economic potential due to the medicinal properties, timber, ornamental and food. The objective was to establish in vitro culture and long-term conservation of Alibertia sessilis Schum, as well as long-term conservation also to Alibertia edulis Rich. In seeds of A. sessilis was performed the caracterization of the water imbibing curve. For the analysis of the chemical composition were held the ether extract determinations, protein, fiber, ash, moisture content, starch, reducing sugar, non-reducing sugar and total soluble sugar. For cultivation in vitro seeds were inoculated in MS culture. In shoot induction were used nodal segments inoculated with different concentrations of BAP (0,0; 0,62; 1,25; 2,5; 5,0 and 10,0 mM). For induction of callus foliar explants were excised and inoculated with different concentrations of 2,4-D and Picloram (0,0; 2,5; 5,0; 10,0 and 20,0 mM). In order to induce calluses on alternative explants, shoot tips were inoculated at different concentrations of 2,4-D (0,0; 2,5; 5,0; 10,0 and 20,0 mM). For cryopreservation of seeds was determined water content, and then dehydration was carried out on silica gel to periods of 0, 15, 30, 60 and 90 minutes and it was later made immersion in liquid nitrogen. The embryos were, then, excised and subjected to droplet vitrification technique, to carry out the cryopreservation of zygotic embryos. Already in A. edulis seed was determined water content, and then dehydration was carried out on silica gel to periods of 0, 10, 20, 40 and 60 minutes and after that the seeds were immersed in liquid nitrogen, after 60 days of cryopreservation the germinated seedlings were acclimatized. A. sessilis seeds have a moisture 31,16% which are classified as starch because of its starch content 16%. The in vitro germination of A. sessilis seeds was 93% at 30 days in MS medium. The optimum concentration for induction estimated shoots in nodal segments was 8.0 mM of BAP. For induction of callus from leaf segments estimated optimal concentrati on is 12,67 mM of 2,4-D. For callus induction in shoot tip the optimum estimated concentration was 12,42 mM of 2,4-D. The seeds and embryos of A. sessilis did not survive the cryopreservation in liquid nitrogen, however, both showed positive responses in question survival to dehydration. To obtain maximal survival A. edulis seed after cryopreservation recommended dehydration silica gel for 73 minutes.